BUSINESS ETHICS AS A PART OF A CONTEMPORARY BUSINESS STRATEGY: STUDY IN THEORETICAL PERSPECTIVE - REJEKIA VAIZAL SIMANUNGKALIT; HARKIM; MAYA ANDRIANI (CV KULTURA DIGITAL MEDIA, 2020)
In the business world, a failure can be triggered by a mistake in determining and implementing a strategy. Various cases show how business failure can occur in an increasingly complex industrial and market structure. One thing that is certain in the complexity of business is competition. Competition is increasingly complicated and tighter, of course, requires the right business strategy. However, on the other hand, ethical strategies may occur in order to maintain the existence of a business. Furthermore, in a contemporary business reality like this, the role of ethics is very much needed. Ethics provide space for dialogue for business complexity and competition. This paper will discuss theoretically the role of ethics as a business strategy in the contemporary business climate. This is a reflective article using experts perspective about business ethic. The main data sourced form journals text, books, and digital sources such as expert blog and so on. All data will be categorized and analyzed to get the spirit of ethic that must be present at the business activity.